Cross-linked chitosan/lysozyme hydrogels with inherent antibacterial activity and tuneable drug release properties for cutaneous drug administration. Issue 1 (31st December 2023) - Lai, Wing-Fu; Reddy, Obireddy Sreekanth; Zhang, Dahong; Wu, Haicui; Wong, Wing-Tak
ABSTRACT: Gels with high drug release sustainability and intrinsic antibacterial properties are of high practical potential for cutaneous drug administration, particularly for wound care and skin disease treatment. This study reports the generation and characterization of gels formed by 1, 5-pentanedial-mediated crosslinking between chitosan and lysozyme for cutaneous drug delivery. Structures of the gels are characterized by using scanning electron microscopy, X-ray diffractometry and Fourier-transform infrared spectroscopy. An increase in the mass percentage of lysozyme leads to an increase in the swelling ratio and erosion susceptibility of the resulting gels. The drug delivery performance of the gels can be changed simply by manipulating the chitosan/lysozyme mass-to-mass ratio, with an increase in the mass percentage of lysozyme leading to a decline in the encapsulation efficiency and drug release sustainability of the gels. Not only do all gels tested in this study show negligible toxicity in NIH/3T3 fibroblasts, they also demonstrate intrinsic antibacterial effects against both Gram-negative and Gram-positive bacteria, with the magnitude of the effect being positively related to the mass percentage of lysozyme. All these warrant the gels to be further developed as intrinsically antibacterial carriers for cutaneous drug administration. GRAPHICAL ABSTRACT: uf0001